2017
DOI: 10.3832/ifor2302-010
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan oligosaccharide addition affects current-year shoot of post-transplant Buddhist pine (Podocarpus macrophyllus) seedlings under contrasting photoperiods

Abstract: (2) Chitosan oligosaccharides (COS) have been used as modifiers to promote growth and mineral nutrient utilization in crop plants, but its over-year effect on current-year shoot (CYS) of juvenile trees is still unclear. In this study, Buddhist pine (Podocarpus macrophyllus) seedlings were cultured under natural and extended photoperiods with or without COS addition for one year. In the following spring, parameters of leaf length, biomass accumulation, and N content in CYS were found to be increased by COS addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
2
28
2
Order By: Relevance
“…We did not find a significant effect of CO addition on biomass in Fragrant rosewood seedlings. In accordance with our study, CO addition also had no effect on Buddhist pine and Northeast yew seedlings [33,34]. However, our results presented that CO addition decreased the stem sugar concentration with no effect on starch (Figure 4b).…”
Section: Carbohydrate Metabolismsupporting
confidence: 73%
See 4 more Smart Citations
“…We did not find a significant effect of CO addition on biomass in Fragrant rosewood seedlings. In accordance with our study, CO addition also had no effect on Buddhist pine and Northeast yew seedlings [33,34]. However, our results presented that CO addition decreased the stem sugar concentration with no effect on starch (Figure 4b).…”
Section: Carbohydrate Metabolismsupporting
confidence: 73%
“…In contrast, Wang et al did not find any significant response of RCD in current-season Buddhist pine and Northeast yew seedlings for the interaction between photoperiod and CO addition [34]. However, Wang et al reported that the interaction between CO addition and extended photoperiod in the past-season can have a continuous effect on RCD in current-season Buddhist pine seedlings after transplant [33]. Also, seedlings receiving CO addition under the natural illumination had a decreased RCD value compared to those under the extended photoperiod by HPS lamps [33].…”
Section: Seedling Shoot Growthmentioning
confidence: 97%
See 3 more Smart Citations